La colonisation militaire en Phrygie (IVe siècle avant-IIIe siècle après J.-C.). Tome 2 : corpora Dynamiques spatiales, économiques et sociales - Roux, Michel (Histoire & Épigraphie, 2023)
The second volume of this book intends to present to the reader all the very many documents on which this historical reflection was based. It does not claim to be exhaustive but seeks to provide in the easiest way possible, that is, community by community, all the epigraphic and numismatic data, very scattered at the outset, that the author was able to gather. A brief presentation at the beginning of each corpus will help to understand the classification system of these texts and coins.